Development of a human induced pluripotent stem cells (hiPSCs)-derived, universal platform, for generation of immunocompetent multi-tissue organoids - Azis, Rizal (2024)
Human induced pluripotent stem cells (hiPSCs) provide a platform that can be used for disease modelling and developing a better understanding of developmental biology. Traditional two-dimensional (2D) co-culture of different cell types derived from hiPSCs is the simplest platform for modelling multicellular tissue similar to an in vitro model, however, these 2D co-cultures are not always physiologically relevant and fail to reproduce tissue complexity, especially in terms of 3D architecture. The interplay or cell-cell interaction between non-parenchymal cells including macrophages, fibroblasts, and endothelial cell and parenchymal cells (tissue-specific epithelial cells) exhibits crucial regulatory activity of tissue homeostasis, yet current in vitro models to not capture this and therefore it needs to rely on non-human animal models to better understand this interplay. To bridge this gap, highly efficient protocols are required to generate different cell types and combined them as 3D organoids for more accurate and human-specific disease modelling and other applications are desperately needed.